The city and the railway in the world from the nineteenth century to the present - Roth, Ralf, 1957-; Van Heesvelde, Paul (Routledge studies in modern history, 2023)
"This volume explores the relationship between cities and railways over three centuries. Despite their nearly 200-year existence, The City and the Railway in the World shows that urban railways are still politically and historically important to the modern world. The City and the Railway in the World will be a useful tool for scholars interested in the history of transport, travel, and urban change"--